Unveiling sustainable agriculture dynamics: a socio-psychological exploration among smallholder farmers in Sikkim, India - Roshan Raj Bhujel; H.G. Joshi (Cogent Social Sciences, 2024)
In response to global calls for environmentally sustainable and socially equitable agriculture, this study examines the socio-psychological factors influencing smallholder farmers in Sikkim, India, to adopt sustainable agricultural practices (SAP). Traditional agricultural methods prioritize productivity over ecological sustainability. SAP addresses this challenge holistically by considering environmental, social, and economic factors. The factors that influence smallholder farmers’ SAP adoption, especially in unique regional contexts, are poorly understood. This study uses the theory of planned behavior (TPB) and social norms theory to examine SAP adoption’s socio-psychological aspects. Sikkim’s sociocultural and agroecological characteristics are studied. Findings show that attitudes (ATs), social norms and perceived behavioral control (PBC) shape SAP adoption intentions (INs), with gender-specific dynamics, age-related nuances and complex socioeconomic factors. This study answers the comprehensive question: ‘What socio-psychological factors influence smallholder farmers in Sikkim, India, to adopt Sustainable Agricultural Practices?’ using quantitative surveys and PLS-SEM analysis of 407 smallholder farmers. In broader conclusion, the study suggests local governments, NGOs, development practitioners, researchers and stakeholders tailor sustainability interventions. This socio-psychological study addresses critical SAP adoption gaps by shifting from behavioral analyses. The main takeaway is that interventions must consider smallholder farmers’ diverse motivations and contextual factors when adopting SAPs. This study advances regional literature and sustainable agriculture discourse, promoting a socially equitable agricultural future.